Edukasi Pencegahan Bullying di SMP Queen Al-Amin, Desa Cintamulya, Kecamatan Candipuro, Kabupaten Lampung Selatan - Huda, Kholis Khoirul; Arfandi, Olau M Reza; Fatmasari, Sindi; Levana, Dhea; Adiningrum, Yoan Fauziah (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2024)
This study evaluates the effectiveness of bullying prevention socialization conducted at SMP Queen Al-Amin, Desa Cintamulya, Kecamatan Candipuro, South Lampung. The socialization aimed to improve the understanding of seventh-grade students about bullying, particularly verbal bullying, using PowerPoint presentations and other supporting equipment. Held on August 1, 2024, the socialization resulted in a significant increase in students' knowledge about bullying. Initially, many students lacked a clear understanding of bullying definitions and forms. Post-socialization, students gained a better grasp of verbal bullying, which includes mocking, derogatory nicknames, threats, insults, and gossip. Interviews revealed frequent experiences or observations of verbal bullying among students, impacting their self-esteem. The socialization successfully raised awareness about the negative effects of bullying and encouraged students to report incidents. The positive change in students' attitudes indicates the effectiveness of the activity in reducing bullying incidents. The role of schools and government policies, such as the Ministry of Education Regulation No. 12 of 2011 on Child-Friendly Schools, is crucial for creating a safe and supportive school environment.